(untitled) (Vietnam Journal of Community Medicine, 2026)
Background Extubation in patients with traumatic brain injury is a challenging clinical decision. Extubation failure increases the risk of pneumonia, prolongs mechanical ventilation duration, and increases mortality. Conventional weaning criteria do not adequately reflect airway protection ability and neurological recovery. The ENIO score integrates neurological and respiratory factors to support the prediction of extubation outcomes. However, the ENIO score has not been widely studied in Vietnam. Objective To analyze factors associated with extubation outcomes and evaluate the value of the ENIO score in predicting extubation success in patients with traumatic brain injury. Methods A retrospective descriptive study was conducted at the Center of Anesthesia and Intensive Care, Bach Mai Hospital, from January 2025 to October 2025. The study included patients with brain injury, Glasgow Coma Scale (GCS) score ≤12, and invasive mechanical ventilation for more than 24 hours. Patients underwent extubation after successful weaning from mechanical ventilation. Outcomes were classified as successful or failed extubation within 5 days after extubation. Results Among 111 studied patients, 75 patients (67.6%) had successful extubation, while 36 patients (32.4%) experienced extubation failure. Factors associated with successful extubation included strong cough reflex (81.3% vs. 33.3%; p<0.001), higher motor GCS score (p=0.006), and lower frequency of sputum suctioning (p<0.001). The ENIO score was significantly higher in the successful extubation group compared with the failure group (median 63 vs. 39), indicating good discriminative ability of the ENIO score for extubation outcomes. Conclusion The simplified ENIO score is a useful tool for predicting extubation outcomes. Factors strongly associated with extubation success include strong cough reflex, lower sputum suctioning requirement, and higher motor GCS score. The ENIO score should be combined with clinical assessment, particularly cough reflex and motor GCS evaluation, to support safer extubation decisions in patients with traumatic brain injury.